IMPACT OF IMPLEMENTING MULTIPLEX ASSAYS AND SYNDROMIC TESTING PANELS ON IMPROVING DIAGNOSTIC EFFICIENCY: REVIEW - Ali Yahya Zofrah, ‏ Hamsa Ruby Saad, ‏ Hadi Hames Al Abass, ‏Hamad yahia AL abbas, Mohammad Saad Abdullah Al-Amri, Faisal Abdulrhman Alyazydi, Mosa Hadi Alayed, Hussam Mohammed Munshet, Mohammed Hajer Almuntasheri, ,; Ayid Saad Nahis, Ahmad Hajer Almuntasheri, ‏Hamoud Awadh Al Enazi, ‏Abdullah Al Himidi Alreshidi, ‏Khaled Fahad Al Bahout, Mohammrd Suleiman Alshamery, (Chelonian Research Foundation, 2022)
The emergence of commercial panel-based molecular testing has revolutionized clinical microbiology and practice by enabling quick pathogen diagnosis in positive blood culture containers, pulmonary samples, stool, and cerebrospinal fluid. This analysis specifically examines multiplex molecular panels that have been authorized or certified by the U.S. Food and Drug Administration (FDA). These panels are meant to diagnose infections in bloodstreams, respiratory tract, gastrointestinal system, or central nervous system, and they target more than five specific pathogens. Although panel-based assays offer the benefits of quick results and the ability to detect a wide range of microorganisms, they also come with challenges such as cost and determining the best strategies for test utilization and interpretation. Keywords: panel-based molecular testing, pathogen diagnosis, pulmonary samples, blood culture containers, review.